Uncaria tomentosa Aqueous-ethanol Extract Triggers an Immunomodulation toward a Th2 Cytokine Profile - Domingues, Alexandre [UNESP]; Sartori, Alexandrina [UNESP]; Marino Valente, Ligia Maria; Golim, Marjorie de Assis [UNESP]; Siani, Antonio Carlos; Viero, Rosa Marlene [UNESP] (Wiley-Blackwell, 2011)
Uncaria tomentosa (Willd.) DC (Rubiaceae) is a large woody vine that is native to the Amazon and Central American rainforests and is used widely in traditional medicine for its immunomodulatory and antiinflammatory activities. The present work used in vivo immunotoxic and in vitro immunomodulatory experiments to investigate the effects of a pentacyclic oxindole alkaloid extract from U. tomentosa bark on lymphocyte phenotype, Th1/Th2 cytokine production, cellular proliferation and cytotoxicity. For the in vivo immunotoxicity testing, BALB/c male mice were treated once a day with 125, 500 or 1250mg/kg of U. tomentosa extract for 28 days. For the in vitro protocol, lymphocytes were cultured with 10-500 mu g/mg of the extract for 48 h. The extract increased the cellularity of splenic white pulp and the thymic medulla and increased the number of T helper lymphocytes and B lymphocytes. Also, a large stimulatory effect on lymphocyte viability was observed. However, mitogen-induced T lymphocyte proliferation was significantly inhibited at higher concentrations of U. tomentosa extract. Furthermore, an immunological polarization toward a Th2 cytokine profile was observed. These results suggest that the U. tomentosa aqueous-ethanol extract was not immunotoxic to mice and was able to modulate distinct patterns of the immune system in a dose-dependent manner. Copyright (C) 2011 John Wiley & Sons, Ltd.
Keywords: Uncaria tomentosa; immune system; mice; immunotoxicity; cytokines; immunophenotype